2008
DOI: 10.1158/0008-5472.can-08-1648
|View full text |Cite
|
Sign up to set email alerts
|

TGFBI Deficiency Predisposes Mice to Spontaneous Tumor Development

Abstract: Loss of TGFBI, a secreted protein induced by transforming growth factor-b, has been implicated in cell proliferation, tumor progression, and angiogenesis by in vitro studies. However, in vivo antitumor functions of TGFBI as well as the underlying molecular mechanism are not well understood. To these aims, we have generated a mouse model with disruption of TGFBI genomic locus. Mice lacking TGFBI show a retarded growth and are prone to spontaneous tumors and 7,12-dimethylbenz(a)anthracene-induced skin tumors. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 47 publications
2
96
0
Order By: Relevance
“…Thus, the physiological expression of PITX1, TGF␤I, and ELL2 mRNA negatively correlated with mtert mRNA expression in the B16F10 clones. TGF␤I encodes a secreted protein, transforming growth factor ␤ (TGF␤), that is known to be a regulator of telomerase activity through the repression of the hTERT gene (57). ELL2 encodes a member of the ELL family of RNA polymerase II elongation factors.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the physiological expression of PITX1, TGF␤I, and ELL2 mRNA negatively correlated with mtert mRNA expression in the B16F10 clones. TGF␤I encodes a secreted protein, transforming growth factor ␤ (TGF␤), that is known to be a regulator of telomerase activity through the repression of the hTERT gene (57). ELL2 encodes a member of the ELL family of RNA polymerase II elongation factors.…”
Section: Resultsmentioning
confidence: 99%
“…␤ig-h3 protein suppresses human breast tumor progression and malignant transformation of cells (27, 34 -38). Mutation or altered expression of ␤ig-h3 has been linked to the pathogenesis of human corneal dystrophy and osteogenesis (39). However, the underlying molecular mechanism of ␤ig-h3 effects is not well understood.…”
mentioning
confidence: 99%
“…One possibility that we examined is that BIGH3 functions as a tumor suppressor that diminishes tumor viability by induction of apoptosis. In support of this possibility TGFBI −/− mice are predisposed to form tumors when compared to wild type mice [10]. Other investigators have shown that BIGH3 is downregulated in tumors and tumor cells of mesenchyme origin, indicating a tumor suppressor role [9] [58] [59] [60] [61] [62].…”
Section: Discussionmentioning
confidence: 99%
“…TGFBI −/− mice exhibited predisposition to develop various tumors, underscoring BIGH3's tumor suppressing property. Isolated TGFBI −/− mouse embryonic fibroblasts showed chromosomal abnormalities, increased cyclin D1 synthesis, and cell proliferation [10].…”
Section: Introductionmentioning
confidence: 97%